English language teaching materials : theory and practice - Harwood, Nigel (New York : Cambridge University Press, 2010)
"This volume provides an incisive overview of the current state of materials design in language teaching. Seventeen original chapters explore the issues involved in the design, implementation, and evaluation of materials in language programs in a wide variety of settings and contexts. This stimulating collection considers different approaches to materials design - including teacher-developed classroom materials, commercial materials, and technology-driven materials. Discussion questions and tasks follow each chapter to make this volume useful to both prospective and practicing teachers alike"--Provided by publisher.
Machine generated contents note: Part I. Introduction: 1. Issues in materials development and design Nigel Harwood; Part II. Perspectives on Materials: 2. Second language acquisition research and language teaching materials Rod Ellis; 3. The theory and practice of technology in materials development and task design Hayo Reinders and Cynthia White; 4. Principles of successful materials development Brian Tomlinson; 5. Critical praxis as materials development: responding to military recruitment on a U.S. campus Sarah Benesch; Part III. Materials for the Language Syllabus: 6. A principled approach to content-based materials development for reading Norman Evans, K. James Hartshorn, and Neil J. Anderson; 7. A genre-based approach to developing materials for writing Chris Tribble; 8. Listening as process: learning activities for self-appraisal and self-regulation Christine Goh; 9. Materials to develop the speaking skill Rebecca Hughes; 10. Developing materials for discipline-specific vocabulary and phrases in academic seminars Martha Jones & Norbert Schmitt; Part IV. Materials for Specific and Academic Purposes: 11. Materials for university essay writing Martin Hewings; 12. Writing for publication: corpus-informed materials for post-doctoral fellows in perinatology Chris Feak & John Swales; 13. Research-based materials to demystify academic citation for postgraduates Nigel Harwood; 14. Making professional academic writing practices visible: designing research-based heuristics to support English-medium text production Mary Jane Curry & Theresa Lillis; 15. English for nursing: developing discipline-specific materials Susan Bosher; 16. Using textbook and real life data to teach turn taking in business meetings Jo Angouri; 17. Designing materials for community-based adult ESL programs Cori Jakubiak and Linda Harklau.
Includes bibliographical references and indexes.
Keywords: English language -- Study and teaching -- Foreign speakers